The Relevance of Stoic Principles and Contentment According to Hadith in Kutub Al-Sittah - Khairul Fajri; Syarifah Mudrika (Program Studi Ilmu Hadis Fakultas Ushuluddin Adab dan Dakwah IAIN Langsa, 2024)
This article explores the philosophy of stoicism, widely embraced and studied by millennials as a means to address life challenges. The primary aim of this study was to examine the relationship between stoicism and the concept of qana'ah in Islamic teachings, as reflected in the Hadiths of the Kutub Al-Sittah. The analysis focused on Hadiths transmitted by Bukhari on the wealth of the heart, Tirmidhi on qana'ah, and Ibn Majah on the virtues of wara' and asceticism. The findings reveal that both qana'ah and stoicism emphasize self-control in responding to negative emotions and psychological disturbances. They also underscore the distinction between what can be controlled and what cannot, urging individuals to refrain from dwelling on uncontrollable factors. Additionally, both philosophies advocate gratitude, positive assumptions (husnudzan), and sincere acceptance of circumstances, whether favorable or not. Despite their similarities, stoicism primarily centers on self-control, whereas qana'ah consistently incorporates divine values into every aspect of life events. In conclusion, stoic teachings bear a significant resemblance to qana'ah teachings found in the Hadiths of the Prophet Muhammad. This piece offers novel perspectives on the evolution of spiritual thought in the intricate context of modernity.